Exploring teachers’ practices when using formative assessment in improving quality education - Bongani B. Ndlovu (Cogent Education)
The study sought to explore teachers’ practices in improving quality education by looking at how teachers are using constructive feedback in formative assessment to improve learner performance. The focus was on what teachers understand about quality education, formative assessment, and the use of constructive feedback to improve quality education. In grade 12 Accounting formative assessments are set or prepared externally days or months before they are used during pre-scheduled time in anticipation that learners would have covered the required content. The study is qualitative in nature. All schools with grade 12 Accounting in the Norther Cape Province, Francis Baard District formed the population of the study. A total of 15 grade 12 Accounting teachers were conveniently selected and interviewed. Interviews were voice recorded, and notes were handwritten. The transcribed notes were then summarized and categorized in accordance with research questions. The findings of this study are that teachers understand what quality education is and how it can be achieved. According to participants quality education is about the achievement of the exit level outcomes that were formulated during program design. The conclusion drawn is that formative assessment activities should be prepared by teachers to address learners’ challenges as they arise. Teachers should embrace provision of feedback as part of teaching and learning and they need to get training on how to provide feedback in class. Future studies need to look at teachers’ practices in providing meaningful feedback, and also devise strategies to measure the impact of feedback in learners’ performance.